1990
DOI: 10.1111/j.1439-0450.1990.tb01117.x
|View full text |Cite
|
Sign up to set email alerts
|

Antibiogram of Staphylococcal Strains Isolated from Milk and Milk‐Products

Abstract: Summary A study of the resistance patterns of 248 staphylococcal isolates from milk and milk products to eight antimicrobial agents using the disc method showed that 80 (32.3 %) were resistant to sulphafurazole, 75 (30.2 %) to penicillin G, 63 (25.4 %) to ampicillin, 23 (9.3 %) to cloxacillin, 19 (7.7 %) to tetracycline, 17 (6.9%) to streptomycin, 14 (5.6%) to erythromycin and 12 (4.8%) to chloramphenicol. One hundred and sixteen (46.8 %) of the 248 staphylococcal isolates were sensitive to all the agents test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
2

Year Published

2001
2001
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 13 publications
2
17
2
Order By: Relevance
“…Comparatively higher prevalence of resistance to antimicrobial agents amongst S. aureus strains have been reported by others (Gentilini, Demamiel, Llorente, & Godaly, 2000;Shitandi & Sternesjo, 2004;Umoh et al, 1990b).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Comparatively higher prevalence of resistance to antimicrobial agents amongst S. aureus strains have been reported by others (Gentilini, Demamiel, Llorente, & Godaly, 2000;Shitandi & Sternesjo, 2004;Umoh et al, 1990b).…”
Section: Discussionmentioning
confidence: 88%
“…The antimicrobial resistance of S. aureus and E. coli recovered from raw milk and milk products have been documented by others (Adesiyun, Webb, Romain, & Kaminjolo, 1997;Makovec & Ruegg, 2003;Pitkala, Haveri, Pyorala, & Myllys, 2004;Umoh, Adesiyun, & Gomwalk, 1990b) and it has also been reported that misuse or abuse of antimicrobial agents could result in resistant strains of bacteria in veterinary medicine (Washington, 1979).…”
Section: Introductionmentioning
confidence: 97%
“…The number of antibiotics involved in the multiple drug resistance as obtained in this study, falls within the range obtained by earlier workers (Grewal and Tiwari, 1990;Singh et al, 1995;Khan and Malik, 2001). The relatively high level of resistance to antimicrobial agents could be a reflection of misuse or abuse of these agents in the environment (Umoh et al, 1990;Abbar and Kaddar, 1991;Silva and Hoffer, 1993;Malik and Ahmad, 1994). Antibiotic prescriptions in hospitals are given without clear evidence of infection or adequate medical indication.…”
Section: Resultsmentioning
confidence: 97%
“…The results of the antibiotic sensitivity test were interpreted and are presented as the resistance of bacterial isolates to the antibiotics (Table 1), and the antibiotic resistance pattern among the bacterial isolates (Table 2). In several earlier works on similar studies carried out on foodstuffs including orange juices, researches have been focused mainly on the strains of E. coli and S. aureus (Umoh et al, 1990;Grewal and Tiwari, 1990;Abbar and Kaddar, 1991;Singh et al, 1995;Desai and Kamat, 1998;Leegar et al, 1999;Silva et al, 2000;Rahman Khan and Malik, 2001). However, in this work, a broad overview of the study was conducted and this is why the resistance pattern and the mechanisms in selected strains of all the bacteria isolated from the orange juices were studied.…”
Section: Resultsmentioning
confidence: 99%
“…In several studies that have been conducted on the resistance of food-borne pathogens, emphasis had been on E. coli and S. aureus (Umoh et al, 1990;Grewal and Tiwari, 1990;Abbar and Kaddar, 1991;Singh et al, 1995;Desai and Kamat, 1998;Leegar et al, 1999;Silva et al, 2000;Rahman Khan and Malik, 2001). However, in the present study, an attempt was made to evaluate the resistance of selected strains of all the bacterial strains that were isolated from the orange fruit products.…”
Section: Introductionmentioning
confidence: 99%